Circulating miR‐22‐5p and miR‐122‐5p are promising novel biomarkers for diagnosis of acute myocardial infarction. Issue 4 (7th September 2018) - Wang, Yu; Chang, Wenguang; Zhang, Yuan; Zhang, Lei; Ding, Han; Qi, Hongzhao; Xue, Sheng; Yu, Hua; Hu, Longgang; Liu, Dacheng; Zhu, Wenjie; Wang, Yin; et al.
Abstract: Background/Aims: This study sought to evaluate the potential of circulating microRNAs (miRNAs) as novel indicators for acute myocardial infarction (AMI). Methods: Plasma samples were collected from each participant, and total RNA was extracted. Quantitative real‐time polymerase chain reaction were used to investigate the expression of circulating miRNAs. We measured circulating levels of six individual miRNAs, which are known to be relevant to AMI, in the plasma samples from 66 AMI patients and 70 non‐AMI healthy comparisons. Results: Five small RNAs were specifically expressed in AMI patients, plasma miR‐122‐5p levels is significantly elevated ( p  < 0.0001) in AMI patients, while plasma miR‐22‐5p ( p  < 0.05) levels were significantly decreased. In addition, significant correlations between miR‐22‐5p and miR‐122‐5p ( R  = 0.773), miR‐122‐5p and creatine kinase isoenzyme (CK‐MB; R  = 0.6296) were detected. Further, receiver operating characteristic (ROC) analysis indicated that miR‐22‐5p showed considerable diagnostic efficiency for predicting AMI (area under the curve [AUC] = 0.975). Combining miR‐22‐5p and miR‐122‐5p in a panel increased the sensitivity (98.6%) of distinguishing between patients with AMI and healthy comparisons. Conclusion: Circulating miR‐22‐5p and miR‐122‐5p could be considered promising novel diagnostic biomarkers for AMI. Abstract : The expression levels of circulating miR‐22‐5p were significantly downregulated, while miR‐122‐5p were significantly upregulated in the acute myocardial infarction (AMI) patients. The results before and after surgery showed that miR‐22‐5p and miR‐122‐5p had a certain degree of recovery. By receiver operating characteristic analyses, we found that the combination of miR‐22‐5p and miR‐122‐5p may be promising predictors of AMI.